Actualization of Andragogical Learning Strategies for Higher Education in Disruption Era - Sufirmansyah, Sufirmansyah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
This article examines the actualization of andragogical learning strategies for higher education in disruption era. Disruption era as an effect of globalization demands optimal integrity of an individual so that they can live their lives well. College students as adult learners are expected to be able to interpret and work around so that the learning they do can run effectively for their future. The library research qualitative approach is chosen in order to compile various relevant references related to andragogical learning strategies in a holistic manner. Based on studies from several references, it can be concluded that andragogy is very relevant to the needs of college students as adult learners. Desire to learn, ability to learn, means to learn, and need to learn become the consideration of the relevance of the concept of andragogy to the needs of college students. On the other hand, the principle of andragogy is also very synergistic with the development of learning independence from a learner. The development of a very rapid disruption era led to changes in learning patterns, from teacher centered to student centered. The andragogical learning process must consider the learner's needs and some aspects of individuality as uniqueness and potential that must be developed. The assumptions that underlie andagoogical learning strategies in tertiary institutions are that students must understand their learning orientation, have a responsible self-concept, learn their life experiences, realize their readiness to learn, learn in concrete, and strengthen their intrinsic motivation. The actualization of andragogical learning strategies can be maximized by studying the learning process contextually, increasing participation in learning, and utilizing the advancement of science and technology. The internet must be optimized as a learning aid so that college students can understand the current conditions of the environment that they will face in the real world. Thus, the demands of the disruption era can be overcome through the actualization of andragogical learning strategies.